Kemampuan Menulis Teks Eksplanasi Dengan Menggunakan Media Gambar Peristiwa: (Studi Pada Siswa Kelas VIIIC SMP Negeri 1 Tungkal Ulu Tahun Ajaran 2023-2024) - Ruth Meiranti (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
This research aims to describe the ability to write explanatory text using image media of class VIII C students at SMPN 1 Tungkal Ulu. This research was conducted at SMPN 1 Tungkal Ulu. This research uses a descriptive qualitative approach. The population in this study were all students in class VIII of SMP Negeri 1 Tungkal Ulu. The sample in this research was class VIII C of SMP Negeri 1 Tungkal Ulu. The data collection instrument in this research was a written test in the form of an assignment to write explanatory text based on its structure. The technique for analyzing data in this research is by assessing students' writing one by one by assessor 1, namely the Indonesian Language subject teacher and assessor 2 (researcher). The results of the research show that the ability to write explanatory text using image media. Class VIII C students of SMP Negeri 1 Tungkal Ulu were rated as very capable. This is proven by the average score obtained from assessor 1 and assessor 2 of 89.92 for writing explanatory text from the general identification structure, cause and effect sequence, interpretation. This value has been categorized as very capable which can be seen from the value interval table which is in the interval 85-100. From the results of this research, it is recommended that teachers increase the use of varied learning media so that they can increase students' motivation and interest in learning. Students should be able to utilize image media as a medium for learning and seeking information about the lesson activities being carried out. The use of this image media can provide new learning experiences to students so that they can be more motivated in learning so that they can improve students' learning outcomes.